Preclinical Studies and Clinical Trials with Mesenchymal Stem Cell for Demyelinating Diseases: A Systematic Review - Esmaeilizade, Zahra; Mohammadi, Bahar; Omrani, Mir D.; Ghaderian, Sayyed M. H.; Rajabibazl, Masoumeh; Fazeli, Zahra (Current Stem Cell Research & Therapy, 2021)
Aim: Different studies have been performed to investigate stem cell administration as a promising tool for recovery of injured tissue in multiple sclerosis (MS), the most common demyelinating disease. Methods: In the present systematic review, the electronic databases of PubMed and ScienceDirect were searched to screen English language studies published until April 2020. Results: The results obtained from experimental autoimmune encephalomyelitis (EAE) animals revealed that modified mesenchymal stem cells (MSCs) transplantation was associated with remyelination, inflammation suppression and oligodendrocyte precursor cells regeneration. Clinical trials indicated that 70% of the patients with MS showed disease stabilization following MSCs administration. Conclusion: Although MSC therapy has showed to be effective in the improvement of some patients with MS, designing larger placebo-controlled clinical trials with MSCs expressing immune- regulators or MSCs-exosomes may provide a novel viewpoint in the treatment of MS.
Keywords: remyelination